Inflammation Mediates the Relationship Between BMI and Serum Ferritin Among Women With Normal to High BMI in Azerbaijan but Not Malawi: BRINDA Project. (7th June 2021) - Davis, Jennie; Arnold, Charles; Williams, Anne; Suchdev, Parminder; Young, Melissa; Rajabov, Tamerlan; Engle-Stone, Reina
Abstract: Objectives: Considering the known metabolic relationships between adiposity, inflammation, and iron status, we examined whether inflammation mediates the relationship between BMI and serum ferritin (SF) concentration among women of reproductive age (15–49 years) with normal to high BMI in a low-income country (Malawi) and an upper-middle income country (Azerbaijan). Methods: Cross-sectional survey data were analyzed from the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) project. Women with underweight (BMI <18.5 kg/m 2 ), pregnancy, or a positive malaria test were excluded (total for analysis: Malawi, n = 594; Azerbaijan, n = 2528). Descriptive statistics were calculated to determine the proportion of women with overweight/obesity (OwOb, BMI ≥ 25 kg/m 2 ), any inflammation (C-reactive protein [CRP] >5 μg/L or α-1-acid glycoprotein [AGP] >1 g/L), and iron deficiency (inflammation-adjusted SF < 15 μg/L). The relationship between BMI and unadjusted SF concentration and potential mediation by CRP and AGP was assessed separately in each country via structural equation modeling procedures, accounting for the complex survey designs. Results: In Malawi, the proportion of women with OwOb was 16%, inflammation 12%, and inflammation-adjusted iron deficiency 14% (12% unadjusted). In Azerbaijan, the proportions were: 57%, 35%, and 45% (31% unadjusted), respectively. In Malawi, BMI was not associated with SF concentration ( P = 0.65). In Azerbaijan, a 1-unit increase in BMI was associated with a 3.3% (95% CI: 2.5, 4.3) increase in SF concentration. Approximately 61% of this relationship was mediated by CRP and AGP, of which 46% was via CRP and 15% via AGP. Conclusions: Iron status is commonly adjusted for inflammation in populations with high expected burden of undernutrition and infectious disease. Considering that obesity is a source of inflammation, these data suggest that measurement and adjustment for inflammation may improve assessment of iron status in populations in which OwOb is common. Funding Sources: Bill & Melinda Gates Foundation, Centers for Disease Control and Prevention, Eunice Kennedy Shriver National Institute of Child Health and Human Development, HarvestPlus, and the United States Agency for International Development.